Vocational Life Skills Students With Disabilities Through Experiential Learning - Siti Mahmudah; Wiwik Widajati; Asri Wijiastuti; Pamuji (Studies in Learning and Teaching, 2023)
Finding out how important experiential learning is for students with disabilities (SwD)'s vocational skills is the primary goal of this study. The purpose of this study is to examine how experiential learning influences students with disabilities' career and occupational capabilities. The professional abilities of a SwD are significantly impacted by this study. The research method is pre experiments and conducted in Surabaya Inclusive Vocational School with subject tens of SwD. The data collection used tes and anlyzed used Wilcoxon test. The result showing Zcount 2.80 > Ztable 1.9 means EL increases VLS SwD results. With the help of the VLS program, effective ELs can easily help teachers, parents, students, and the community. It builds awareness about promoting social skill acquisition for individuals with disabilities, appropriate career, and vocational education. This research result also implication to driving VLF through EL to determine need for futher program to ensure SwD gain success. It builds awareness about promoting social skill acquisition for individuals with disabilities, appropriate career, and vocational education.